Analysis of competitive activity and special technical readiness between football players in age of 10–12 years - Журід Сергій Миколайович (Sergey Zhurid); Лебедєв Сергій Ігорович (Sergey Lebedev); Слеман Ребаз (Rebaz Sleman) (Slobozhanskyi Herald of Science and Sport, 2015)
Purpose: to define the dynamics of technical preparedness and competition activity of young footballers in age 10–12. Material and Methods: analysis and generalization of literary sources; pedagogical supervisions; instrumental method of registration of competition performance indicators; methods of mathematical statistics. In research 24 footballers took part 10–12. Playing activity was analysed during 18 games of championship of s. Kharkiv on football. Results: dynamics of indicators presented by tests: dribbling, stroke counters, shot on goal, dribbling with a stroke 5 laps, juggling, hit the ball on the accuracy. Conclusions: it was determined that the total command of technical and tactical actions (TTA) during competitive activity increases with age. The 10-year-old young players perform per game 324,6±12,3 TTA, at 11-years of age, the figure was 407,1±14,6 TTA, and in 12-years – 433,2±13,8 TTA.